Absurdity and Serendipity: Reclined domain for Innovations and Researchers/Discoveries - Nasir, Tahir (European Journal of Applied Sciences, 2024)
An absurdity is a kind of illogicality and etymologically origin from the Latin word “absurdus-a-um”, means unreasonable or out of place/discordant, etc [1]. Absurdity subsists in an arbitrary campaign besides in the situation arises, being considered as a fiasco to demark an indispensable and meaningful from unnecessary and worthless. Sir Selman Waksman got Albert Lasker award (1948), Nobel Prize (1952) and Leeuwenhoek Medal for their work on antibiotic: streptomycin’s discovery, yet co-researcher Albert Schatz and other scientific community also had considered antibiotic’s finding as an absurdity. Term serendipity recites discoveries being befalling at the juncture of chance and wisdom. Serendipity is the fact-full finding of rather advantageous and/or remarkable may be by fate. Greek mathematician, Archimedes in the 3rd century had validated the principal law of hydrostatics mere by chance while verifying the crown was made of pure gold/cheap alloy when lowered in the water in tub, and then water overflowed and ran out dis-clothed into the street by shouting “Eureka-Eureka/miracle”. Similarly Swiss chemist Albert Hofmann in 1938 had discovered a psychedelic drug Lysergic acid diethylamide (LSD) by accident after unintentional ingestion of strange amount possibly absorbing via skin. Absurdity and serendipity on mutual blending arises many surprises and delightful outcomes. Envisaging a series of absurdity endures incidental results, where the nonsensical elements somehow align perfectly to yield an optimistic and eloquent conclusion. All needs to be stumbled upon a mode and/or a breakthrough in the midst of chaos or irrationality.